The resurrectionist - Dunlap, A. Rae (Kensington Publishing Corp., 2025)
Edinburgh, Scotland, 1828. Naïve but determined James Willoughby has abandoned his posh, sheltered life at Oxford to pursue a lifelong dream of studying surgery in Edinburgh. A shining beacon of medical discovery in the age of New Enlightenment, the city's university offers everything James desires--except the chance to work on a human cadaver. For that, he needs to join one of the private schools in Surgeon's Square, at a cost he cannot afford. In desperation, he strikes a deal with Aneurin "Nye" MacKinnon, a dashing young dissectionist with an artist's eye for anatomy and a reckless passion for knowledge. Nye promises to help him gain the surgical experience he craves--but it doesn't take long for James to realize he's made a devil's bargain . . .Nye is a body snatcher. And James has unwittingly become his accomplice. Intoxicated by Nye and his noble mission, James rapidly descends into the underground ranks of the Resurrectionists--the body snatchers infamous for stealing fresh corpses from churchyards to be used as anatomical specimens. Before he knows it, James is caught up in a life-or-death scheme as rival gangs of snatchers compete in a morbid race for power and prestige. James and Nye soon find themselves in the crosshairs of a shady pair of unscrupulous opportunists known as Burke and Hare, who are dead set on cornering the market, no matter the cost. These unsavory characters will do anything to beat the competition for bodies. Even if it's cold-blooded murder . . .